COMPARATIVE CYTOTOXIC, ANTITUMOR AND ANTI-PROLIFERATIVE ACTIVITIES EVALUATION OF SEA BUCKTHORN (HIPPOPHAE RHAMNOIDES LINN) BERRIES EXTRACTS OF PAKISTAN - Javid Ali; Muhammad Siddique; Arshad Hussain; Javed Abbas; Inayat Ur Rehman; Abdul Wajid Khalil; Muhammad Tayyab Gul; Rehman Ullah; Anwar Zeb; Muhammad Akram; Muhammad Younas; Muhammad Saqib Khalil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The present study was carried out to investigate the antiproliferative, antitumor and cytotoxic potential of sea buckthorn berries from Pakistan. Folin-Ciocalteu reagent method was used to determine the Phenolic compounds, 2, 4 dinitro phenylhydrazine (DNPH) method was applied to quantified the ascorbic acid and cytotoxic activity determined by Artemia salina lethality bioassay method. The flavonoids, Lycopene and β-carotene were estimated spectrophotometrically. The antitumor potato disc assay using Agrobacterium tumefaciens was employ to evaluate the antitumor activities and Methyl thiazolyl tetrazolium (MTT) assay was carried out to determine the anti-proliferative properties. Maximum total phenolic content, flavenoids, ascorbic acid, lycopene and β-carotent were 13±01 mg of Gallic acid/gm, 5.2±0.5 mg of Rutin/gm, 410±4 mg/100g, 25±2 mg/100g and 380±7 µg/g respectively in methanol extract. Highest brine shrimp mortality (73.33%) was observed in methanol extract at 1000 mg/L. Highest tumors inhibition activity (75.00%) was shown by methanol extracts at 1000 mg/L. The highest % cell death of human cervical (HeLa), colorectal adenocarcinoma (Caco-2), prostatic adenocarcinoma (PC-3), stomach adenocarcinoma (AGS) and mammary gland adenocarcinoma (MDA-MB-231) were 75%, 80.71%, 80.00%, 76% and 76.92% respectively in methanol extract. While in ethyl acetate maximum cell death 70.33% for mammary gland adenocarcinoma (MCF-7). The variation in cell inhibition, tumor and cytotoxic activities might be blame to the dissimilar quantification of bioactive compounds accountable for these activities. Every extracts have substantial intensity of antitumor, cytotoxic and cell inhibition with a dose dependant way. The present research outcomes proved that Sea Buckthorn berries extracts an effective natural resource of bioactive compounds with cytotoxic, antitumor and anticancer activities.